A Research on The Social Aspects of Family Physician-Patient Relationship - (:unkn) unknown (INT MANAGEMENT DEVELOPMENT ASSOC-IMDA, 2012)
Good relationships must be established between physicians and patients in order to reach the determined objectives in the new application in Turkey known as family medicine model. In most of the previous researches, it is found out that; physician-patient relationship has an important impact on patients satisfaction. In this study, it is accepted that family physicians success is not only based on their occupational issues. Also their relationship and communication with patients are important key factors that are examined in this social study. This study focusses on the family physicians who live and work in Istanbul. Kind of conveyed information, impacts of these information, their meeting and importance level given to this relationship are tried to test in this study.
Keywords: COMMUNICATION; SATISFACTION